Enhancing wellbeing among pre-service teachers through a mindfulness-based social and emotional learning curriculum: a quasi-experimental study in China - Yunpeng Wu; Liping Qin (Frontiers in Psychology)
BackgroundIntegrating mindfulness practices and Social and Emotional Learning (SEL) into teacher education can significantly enhance educators’ wellbeing, resilience, and effectiveness. However, the cultural specificity of such interventions, particularly in the Chinese educational context, requires careful adaptation and examination.ObjectiveThis study aims to design, implement, and evaluate a culturally adapted MBSEL curriculum for Chinese pre-service teachers. It investigates the program’s effectiveness in improving mindfulness, self-compassion, and life satisfaction, contributing to the literature on integrating mindfulness and SEL in teacher education within a specific cultural setting.MethodsEmploying a quasi-experimental design, the study involved a sample of 41 Chinese pre-service teachers divided into an experimental group (n = 22) and a control group (n = 19). The MBSEL program’s impact on participants’ mindfulness, self-compassion, and life satisfaction was assessed using pre- and post-intervention measures.ResultsThe results of repeated measures analyses of variance indicated significant improvements in mindfulness, self-compassion, and life satisfaction among participants in the experimental group compared to the control group. These outcomes underscore the effectiveness of the culturally adapted MBSEL program in enhancing key aspects of pre-service teachers’ wellbeing and professional readiness.DiscussionThe study demonstrates that a culturally adapted MBSEL curriculum effectively enhances mindfulness, self-compassion, and life satisfaction among Chinese pre-service teachers. This emphasizes the necessity of cultural sensitivity in developing mindfulness and SEL interventions for teacher education. Moreover, the success of the MBSEL program suggests its potential for global integration, urging policymakers and educators to prioritize culturally tailored approaches to enhance teacher wellbeing and educational outcomes.